Molar mass measurement of a 28Si-enriched silicon crystal with high precision secondary ion mass spectrometry (SIMS). Issue 12 (26th September 2022) - Gao, Yu-ya; Ren, Tong-xiang; Williams, Ian S.; Ireland, Trevor R.; Long, Tao; Rienitz, Olaf; Pramann, Axel; Wang, Song; Song, Pan-shu; Wang, Jun
Abstract : Several highly-enriched 28 Si crystals were produced to enable a better determination of the Avogadro constant through removing the uncertainty associated with the abundance determination of the minor isotopes 29 Si and 30 Si. Abstract : Several highly-enriched 28 Si crystals were produced to enable a better determination of the Avogadro constant through removing the uncertainty associated with the abundance determination of the minor isotopes 29 Si and 30 Si. Previous determinations have used inductively coupled plasma mass spectrometry (ICP-MS), which typically requires rather large amounts of material and complex chemical pre-treatment. A secondary ion mass spectrometry (SIMS) protocol for ultra-high precision and accuracy Si isotope measurements of a 28 Si-enriched crystal (AVO28) was developed in this study using a reverse-geometry ion microprobe SHRIMP RG. An ≈8 nA primary beam intensity was used to sputter the 28 Si-enriched crystal. Secondary ions were measured on a combination of Faraday cup, for 28 Si +, and electron multiplier for the low abundance 29 Si + and 30 Si + signals respectively. The secondary ion intensities and isotope ratios were determined following baseline correction, gain correction, tailing correction and instrumental mass fractionation correction. An internal precision of ±0.000016 (2 sm ) and external precision (reproducibility) of ±0.000043 (2 s) were achieved for 29 Si/ 28 Si of spot-to-spot analyses on natural silicon (WASO 04). The Si isotope ratios of AVO28 are n ( 29 Si)/ n ( 28 Si) = 0.00004107(63) mol mol −1 and n ( 30 Si)/ n ( 28 Si) = 0.00000107(4) mol mol −1, 2 s, respectively. As a result, an average molar mass of the AVO28 material was determined to be 27.97696972 g mol −1 with an associated relative standard uncertainty of 1.3 × 10 −8 ( k = 1). This newly developed SIMS method avoids the complex chemical pre-treatment and the molar mass was in good agreement (∼10 −8 ) with solution multi-collection-ICP-MS results.